The Effectiveness of Ultra-Brief Mindfulness Intervention in Distress Reduction - Lim, Kwey Hwa; Loke, Ke Jun (2016)
The effectiveness of ultra-brief mindfulness intervention on distress objectively and subjectively was being examined. Forty participants included 18 males and 22 females with a mean age of 22 years old were recruited and randomly allocated to Mindful STOP or reflective listening which was the control group. The results revealed that there were no significant difference in the subjective level of distress which include SUDS (p = 0.731) and state-anxiety (p = 0.080) between intervention group and control group. Moreover, the result also showed that there was no significant difference in the objective level of distress which include heart rate (p = 0.922), R-R interval (p = 0.682), and SDNN (p = 0.935) between intervention group and control group. Even though the results showed no significant difference in state-mindfulness (p = 0.123) between intervention group and control group at post-test, state-mindfulness significantly increased among control group at post-test. In conclusion, ultra-brief mindfulness intervention which is Mindful STOP is as effective as reflective listening. The implications of this study are discussed.